2015
DOI: 10.1002/jsfa.7361
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐deamidation of soy protein isolate exerts impacts on transglutaminase‐induced glucosamine glycation and cross‐linking as well as properties of the products

Abstract: SPI deamidation decreases forthcoming glycation and cross-linking, and gives the products higher digestibility, less increased hydration, lower thermal stability, and a more open secondary structure. Pre-deamidation is applicable to control the properties of GC-proteins. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In the absence of primary amine, the water would become an acyl receptor, and the glutamine residue removes the amino, which is hydrolyzed into acidic carboxyl groups; this reaction could alter the isoelectric point and solubility of protein (Folk, ). Deamidated proteins contain decreased amount of glutamine residues, which will offer less opportunity for protein cross‐linking induced by MTGase, inevitably, the cross‐linking reaction would be maintained in a less reaction extent (Yao & Zhao, ), and the properties of the cross‐linked product might be influenced by deamidation. Therefore, the mechanism to control the reaction condition should be explored to modify the direction of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of primary amine, the water would become an acyl receptor, and the glutamine residue removes the amino, which is hydrolyzed into acidic carboxyl groups; this reaction could alter the isoelectric point and solubility of protein (Folk, ). Deamidated proteins contain decreased amount of glutamine residues, which will offer less opportunity for protein cross‐linking induced by MTGase, inevitably, the cross‐linking reaction would be maintained in a less reaction extent (Yao & Zhao, ), and the properties of the cross‐linked product might be influenced by deamidation. Therefore, the mechanism to control the reaction condition should be explored to modify the direction of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…After the glycosylation reaction, the peak intensity at around 208 nm decreased (Figure 7b), indicating that the reaction caused a structural change of WPI‐D. The peak intensity at 217 nm after the glycosylation reaction decreased, indicating that the content of the β‐sheet structure was lowered during the reaction (Yao & Zhao, 2016). Lysine residues were mostly present in the β‐sheet structure of proteins, and glycosylation reaction was most likely to occur according to the report lysines 47, 70 and 91 (Fogliano et al., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…(TGase, protein-glutamine: amine -glutamyltransferase, EC 2.3.2.13) is an enzyme that catalyzes post-translation modification of proteins and glycation reaction between protein and amino-containing saccharides. 1,2 The cross-linking effect introduced by TGase may improve the function properties of proteins without altering their nutritional quality. TGase was first extracted from animals in 1973, and subsequent studies showed that this enzyme is widespread in plants and microorganisms.…”
Section: Transglutaminasementioning
confidence: 99%
“…Transglutaminase (TGase, protein‐glutamine: amine γ ‐glutamyltransferase, EC 2.3.2.13) is an enzyme that catalyzes post‐translation modification of proteins and glycation reaction between protein and amino‐containing saccharides . The cross‐linking effect introduced by TGase may improve the function properties of proteins without altering their nutritional quality.…”
Section: Introductionmentioning
confidence: 99%